Yield and compatibility of ten tomato scion varieties grafted with ‘Maxifort’ rootstock - David E Loewen; Eleni D Pliakoni; Cary L Rivard (Urban Food Systems Symposium, 2020)
Many urban and peri-urban tomato growers are adopting the use of grafted plants to help reduce disease incidence and/or improve crop yields, particularly in high tunnel systems. However, little is known about how scion cultivar selection plays a role or if there is a similar impact across scion cultivars in regard to fruit yield. In our study, ten hybrid, determinate, red slicing tomato (Solanum lycopersicum) varieties were evaluated as scions for ‘Maxifort’ rootstock. Trials were conducted in 2016 and 2017 in a three-season high tunnel in Olathe, KS. All ten scion varieties were found to be compatible with ‘Maxifort’. However, ‘BHN 589’, ‘Red Deuce’, ‘Skyway’, and ‘Tasti Lee’ showed significant improvements in marketable yield when grafted to ‘Maxifort’ indicating that they were “highly compatible” with the rootstock. Grafted ‘Red Deuce’ and ‘BHN 589’ scions had the highest fruit yield of any of the treatments that we tested and ranged from to 21.4 to 23.0 lbs of marketable fruit per plant. Nongrafted ‘Primo Red’ was also a good option for high tunnel production and provided 19.2 lbs of marketable fruit per plant. The results of this study suggest that not all scion cultivars respond to grafting with ‘Maxifort’ rootstock in the same manner and we attempted to assess their compatibility based on crop productivity.
Keywords: hoophouse; high tunnel; greenhouse tomato; propagation; splice grafting; tube grafting